2015
DOI: 10.1002/btpr.2079
|View full text |Cite
|
Sign up to set email alerts
|

Generic Raman‐based calibration models enabling real‐time monitoring of cell culture bioreactors

Abstract: Raman-based multivariate calibration models have been developed for real-time in situ monitoring of multiple process parameters within cell culture bioreactors. Developed models are generic, in the sense that they are applicable to various products, media, and cell lines based on Chinese Hamster Ovarian (CHO) host cells, and are scalable to large pilot and manufacturing scales. Several batches using different CHO-based cell lines and corresponding proprietary media and process conditions have been used to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 29 publications
(47 reference statements)
5
81
0
Order By: Relevance
“…The models in the study also used training sample sets but were reported to be generic in the sense that they were scale and process independent, and thus could be used at multiple scales and for various processes (i.e., the methodology worked even if the target cell line had not been used in the initial calibration data set). 164 Since the first offline Raman analysis of spent cell culture media in the late 1990s, the technology has progressed to a point where the bioreactor broth is now analyzed in real time, 159,163 and the yield of a bioprocess could be predicted. 118,165 In 2014, Craven et al demonstrated the next logical step, a Raman analysis that could be used to control a bioprocess; the ''nonlinear model predictive controller'' (NMPC) used online Raman measurements and a closed-loop feedback control system to maintain the glucose concentration at 11 mM inside a CHO bioprocess (15 L) bioreactor (Figure 11).…”
Section: Bioprocess Analysis and Monitoringmentioning
confidence: 99%
“…The models in the study also used training sample sets but were reported to be generic in the sense that they were scale and process independent, and thus could be used at multiple scales and for various processes (i.e., the methodology worked even if the target cell line had not been used in the initial calibration data set). 164 Since the first offline Raman analysis of spent cell culture media in the late 1990s, the technology has progressed to a point where the bioreactor broth is now analyzed in real time, 159,163 and the yield of a bioprocess could be predicted. 118,165 In 2014, Craven et al demonstrated the next logical step, a Raman analysis that could be used to control a bioprocess; the ''nonlinear model predictive controller'' (NMPC) used online Raman measurements and a closed-loop feedback control system to maintain the glucose concentration at 11 mM inside a CHO bioprocess (15 L) bioreactor (Figure 11).…”
Section: Bioprocess Analysis and Monitoringmentioning
confidence: 99%
“…Despite these limitations, PLS-modelling of extracellular metabolomic data demonstrated its potential to predict glycosylation patterns. In large-scale manufacturing particularly, the measurement of extracellular metabolites may be easily and quickly carried out at-line or even on-line, using for instance Raman-based multivariate calibration models 303 . Real-time data rather than off-line analytical testing would be a great benefit in routine manufacturing for both monitoring and control.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-scale transferability of implicit models, for the same bioprocess, was demonstrated within the development scale and from development to manufacturing [83, 84]. A recent study by Mehdizadeh et al successfully demonstrated the use of a generic PCA/PLS model for bioreactors involving CHO cell lines [94]. Model predictions of glucose, lactate, and viable cell density were shown to be adequate for independent validations at the large pilot scale and in a cell line that was not included in model development.…”
Section: Chemometric Modeling Of Bioprocessesmentioning
confidence: 99%